Modeling and of Strengthening Servant Leadership - Andi Hermawan; Sri Setyaningsih; Soewarto Hardhienata (Publikasiku, 2022)
This study aims to produce strategies and ways to strengthen service leadership by analyzing the effect of other variables on servant leadership. The other variables are adversity intelligence, proactive personality, work commitment, team work and work motivation. The research begins by conducting qualitative research to explore factors that are thought to have a positive and dominant influence on the resources to be strengthened. Based on the factors or variables found, the constellation of the effects of these variables on the resources will be strengthened so as to produce research hypotheses.The research hypothesis at the qualitative research stage is then tested using path analysis at the quantitative research stage. The informants in the qualitative research were 16 (sixteen) principals from vocational schools who were the sample sources of research data. Based on the results of the analysis, discussion of research results and hypotheses that have been tested, it can be concluded as follows: Strengthening service leadership can be done by developing adversity intelligence, proactive personality, and teamwork as exogenous variables by increasing commitment to the organization and work motivation as intervening variables. From the qualitative research conducted, it was found that other variables that have a positive and dominant influence on service leadership, namely adversity intelligence, proactive personality, teamwork, commitment to the organization and work motivation